Adsorption of Volatile Carboxylic Acids on Activated Carbon Synthesized from Watermelon Shells - Catalina López-Velandia; Jonathan Julian Moreno-Barbosa; Rocio Sierra-Ramirez; Liliana Giraldo; Juan Carlos Moreno-Piraján (Adsorption Science & Technology)
Because of the high energy costs involved in using the MixAlco process in the separation of fermentation water, it is necessary to implement a separation method in which the absorbates can be adsorbed onto activated carbon (AC). For this purpose, in this study, we synthesized AC from watermelon shells (CAS) and the synthesized carbon was modified with NaOH (CASM) in order to improve its adsorption efficiency. Adsorption kinetic studies of short-chain carboxylic acids (acetic acid, propionic acid and butyric acid) onto the synthesized ACs were performed. The CASM had an adsorption efficiency of 71%, 70% and 63% for acetic acid, propionic acid and butyric acid, respectively. This efficiency was higher than that of CAS, which presented an efficiency of 32%, 30% and 27% for the respective acids. The AC from watermelon shells was synthesized by chemical activation with phosphoric acid (40% wt/wt), producing a yield of 84%. The carbon was modified by adding 10M NaOH. Finally, the physical and chemical characteristics of the synthesized AC were studied, which gave the following results: The surface area was 710 m 2 /g for CAS and 864 m 2 /g for CASM, a microporous and mesoporous structure, pore-size distribution of 0.39–4.54 nm for CAS and 0.39–6.0 nm for CASM, pore volume of 0.26 cm 3 /g for CAS and 0.55 cm 3 /g for CASM. The CAS modification caused an increase in the pore volume with a distribution below 10 nm, an increase in the number of basic groups on the carbon surface and a decrease in the carboxylic groups. All of these factors favoured the adsorption of the acids.